Assessment of occupational radiation dose in interventional settings - Cretti, Fabiola (La Medicina del Lavoro, 2018)
Introduction: In light of both current Italian radioprotection law and the new European Directive, radiation dose monitoring was carried out on the interventional staff, of the new Papa Giovanni XXIII Hospital in Bergamo, Italy, potentially exposed to high radiation levels. Methods: Interventional activities were mapped and personal dose data were collected for three years using thermo-luminescent dosimeters. Effective dose (ED) to whole body and equivalent dose (HT) to hands and eye lenses were estimated from Hp(10) and Hp(0.07) measurements. Results: During the monitoring period, individual annual cumulative ED ranged from 0.2 to 9.3 mSv for radiologists (N=4), from 0.1 to 4.6 mSv for neuroradiologists (N=4), from 0.1 to 2.0 mSv for nurses (N=11), and from less than 0.1 to 1.2 mSv for radiographers (N=14). Individual annual HTs to hands ranged from 1.5 to 282.0 mSv for radiologists, from 0.5 to 99.7 mSv for neuroradiologists, from 1.9 to 12.8 mSv for nurses and from 0.7 to 12 mSv for radiographers. Individual annual HTs to eye lenses ranged from 1.1 to 110.9 mSv, from 0.6 to 58.3 mSv, from 0.1 to 8.6 mSv, from less than 0.1 to 11.7 mSv for radiologists, neuroradiologists, nurses and radiographers respectively. Conclusions: The doses received by medical doctors were higher than those for the other two groups. The Italian dose limits have been respected for all operator categories. The eye lens dose limit of the new European Directive (BSS 2013) was exceeded in 2013 by three medical doctors, prompting prescription of protective glasses. Since 2015 also this new limit has been observed.